If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(-9+x)=-12
We simplify the equation to the form, which is simple to understand
4(-9+x)=-12
Reorder the terms in parentheses
+(-36+4x)=-12
Remove unnecessary parentheses
-36+4x=-12
We move all terms containing x to the left and all other terms to the right.
+4x=-12+36
We simplify left and right side of the equation.
+4x=+24
We divide both sides of the equation by 4 to get x.
x=6
| 60^3/12x=0 | | X^2+54+728=0 | | 6x+8y=98 | | 3(1)+6y=12 | | 3z+6=4 | | 8/11(n-19)=64 | | -4v=-9/5 | | -2(-4x+2)=-12 | | 5x+5.7= | | x+.06x=10.6 | | 90+x=220 | | (3k-2)(2k+1)=k(6k+5)-3 | | x(x)=18 | | 893x-0=4x-2 | | -2x+(x+5)=-7 | | -4x-3=2x-15 | | -10x-10=-2(8x-4) | | (1/4)(t+4)=35 | | -11x+42=7x-12 | | 3(4x-2y)+6y=12 | | 15+12=2u+u | | 2y+50=x+44 | | 60^3/12x | | y-4y=-2 | | 7v=-49 | | -3y-8=10 | | 8(x+5)+3(x+5)=x-6 | | 35=-5/8u | | x+.06x=10 | | 81x^2-7=93 | | 5(x+4)+6=-4 | | 8v-3v=-19-11 |